Ciclagem de nutrientes em coberturas florestais no sul do Espírito Santo - Grugiki, Marilia Alves (2011)
This study aimed to assess the overall nutrient dynamics and their relationship with the input, decomposition and mineralization of litter in the forest canopy of secondary forest, Sapindus saponaria, Acacia mangium and Hevea brasiliensis in the southern state of Espírito Santo. The deposition of litter was measured by installing three collectors (50 x 50 cm) in each forest cover. The material was intercepted by collectors collected monthly during the period from January to October 2010. To quantify the accumulation of litter in the soil was used a template 0.33 x 0.33 m in the months of November/2009, March/2010, November/2010 and June/2010. Both the study of deposition of litter accumulation as in the samples of litter were taken to the laboratory where they were oven dried and weighed, and then determined the levels and stocks of Ca, Mg, P and K. The decomposition of leaf litter was measured using litter bags collected in each forest cover. The remaining material in each litter bags were collected at different periods of time they were weighed to obtain dry matter. For the assessment of microbial activity, proceeded to quantify the CO2 (mineralizable C). The experimental results showed that the forest cover behaved differently regarding the deposition and accumulation of litter, with emphasis on Acacia mangium that, in the dry season, provided greater total litter deposition and rubber, that among the forest canopy, showed the lower performance for both the deposition and to the accumulation of litter. Among the nutrients in litterfall and accumulated phosphorus content did not vary between forest cover, and so on for the potassium content in leaves and magnesium fraction in the fraction of non-leaf litterfall. The accumulation of nutrients was more influenced by litter production than by the nutrient content in the litter. Acacia mangium, together with the secondary forest showed, in general, higher values and rubber, the lowest values. As for the decomposition, the experimental results showed that the forest cover behaved differently in terms of decomposition and microbial activity, with highlights for Sapindus saponaria that had a higher rate of decomposition of total litter and rubber, that among the forest cover, showed the lower rate of decomposition in relation to other coverage. The content of nutrients released in the decomposition of litter produced the downward trend over the day. The coverage of Sapindus saponaria presented for two depths, higher amounts of CO2 accumulated in relation to other forest cover. Coverage of Acacia mangium showed the lowest values accumulated CO2. For this study, among the parameters evaluated, the accumulation of nutrients and the production of litter accumulated and deposited proved as important indicators for assessing nutrient cycling in forest cover